Pulmonary ultrasound-guided management of delayed pulmonary edema secondary to nitric acid fumes inhalation: a case report - Zhenqing Zhao; Yinbing Jin; Huaibao Ma; Mingfeng Lu (BMC Pulmonary Medicine)
Abstract Background Concentrated nitric acid can form nitrogen oxides through a spontaneous redox reaction. After inhalation, it has a stimulating effect on the respiratory tract and can cause inhalation lung injury. This lung injury is mainly manifested as non-cardiogenic pulmonary edema in imaging, and pulmonary ultrasound can dynamically monitor the severity of pulmonary edema at the patient’s bedside. Case presentation This article describes a 52-year-old female case who experienced chest tightness and dyspnea 8 h after inhaling nitric acid fumes and was sent to the emergency room. Chest CT suggested diffuse exudation in both lungs, and dynamic B-lines could be seen by bedside pulmonary ultrasound. During the treatment of this patient, we adjusted the dosage of hormones and the oxygen therapy plan in a timely manner according to the evolution of B-lines under ultrasound. After treatment, her clinical symptoms gradually improved, and the re-examination of chest CT showed that the exudation in both lungs was gradually absorbed. Conclusion This case reminds clinicians to be alert to the occurrence of delayed pulmonary edema when treating patients who inhale nitric acid fumes. At the same time, dynamic examination of bedside pulmonary ultrasound is of great value in the treatment of such patients.